Telephone-based aftercare groups for family carers of people with dementia - results of the effect evaluation of a randomised controlled trial - Martin Berwig; Susanne Lessing; Ruth Deck (BMC, 2022)
Abstract Background The care of people with dementia is associated with enormous stress and, in a quarter of cases, leads to depression and anxiety disorders in the caring relatives. A specially designed inpatient psychosomatic rehabilitation (rehab) programme for family carers of people with dementia has proven to be effective but not sustainable. Therefore, the present study aims to increase the sustainability of the inpatient rehab programme by using thematically structured telephone aftercare group sessions. Methods The effectiveness of telephone aftercare groups was investigated in a randomized, controlled, prospective, mixed methods, longitudinal study. The aftercare intervention included social participation in monthly telephone group sessions for 6 months. The primary outcome was increased social participation of family carers, which, like the secondary outcomes (such as quality of life and subjective health), was assessed in written surveys at three or four measurement points. Results Complete data from 69 participants from the intervention group and from 72 participants from the control group could be evaluated. A small-sized reduction in restrictions on social participation was observed in the intervention group, whereas the reduction in the control group was negligible. The repeated-measures analysis of variance (ANOVA) showed sustained effects on the secondary outcomes, such as depression, perceived social support, and the mental health domain of quality of life of family carers, in favour of the intervention group. The results also showed that telephone-based aftercare groups had a rather minor influence on the use of support services. Except for those from family, friends and neighbours, existing support offers were hardly used. Conclusion Telephone aftercare group sessions for carers of people with dementia were not able to increase social participation at the expected magnitude. Nevertheless, the clear effects on selected secondary health-related outcomes and the assessment of the telephone-based group sessions by the participants show that the caring relatives were able to benefit greatly from this aftercare measure. Family carers should be informed more extensively about the corresponding resources and encouraged to use them. Overall, this new aftercare concept can be recommended for implementation, and its use also seems to be target-oriented for other indications. Clinical trial registration German Clinical Trials Register: DRKS00013736 , 14/05/2018.